FRI0096 Predictive Value of The Multi-Biomarker Disease Activity (MBDA) Score for Flare and Sustained Remission in The Honor Study. (15th July 2016) - Hirata, S.; Tang, S.; Hwang, C.C.; Miyagawa, I.; Kubo, S.; Nakano, K.; Nakayamada, S.; Saito, K.; Defranoux, N.A.; Tanaka, Y.
Abstract : Objectives: To determine the predictive value of the multi-biomarker disease activity (MBDA) (Vectra® DA) score for flare and sustained clinical remission after discontinuation of adalimumab (ADA) in patients with rheumatoid arthritis (RA) from the HONOR study [1, 2]. Methods: This retrospective sub-analysis was conducted on 42 RA patients from the HONOR study. Patients receiving ADA and methotrexate (MTX) who maintained DAS28-ESR remission (<2.6) for ≥24 weeks and who subsequently agreed to discontinue ADA were enrolled. Clinical disease activity, functional status, and joint damage were recorded at ADA discontinuation (baseline), and after 24 and 52 weeks. MBDA scores (remission, ≤25; low, 26–29; moderate, 30–44; high, >44) were determined from serum samples collected at baseline. The ability to predict flare (DAS28-ESR ≥3.2) or sustained clinical remission (SC-REM) (absence of flare with DAS28-ESR <2.6 at all visits) by MBDA score and patient characteristics were determined. Results: At ADA discontinuation, all patients had DAS28-ESR <2.6 with 81% female, 69% RF+, 81% ACPA+ and 30-month mean disease duration. The median MBDA score was 24.5 [quartile; 14.3, 30.8] with 22 (52.4%) patients in remission, and 6 (14.3%) low, 9 (21.4%) moderate and 5 (11.9%) high MBDA score. At 52 weeks, flare and SC-REM were observed in 12/42 (28.6%) and 19/42 (45.2%) patients, respectively. Rate of flare and percentage of SC-REM by MBDA category (remission/low/moderate/high) were 13.6%/50.0%/33.3% and 60.0% (p=0.033) and 63.6%/33.3%/33.3% and 0% (p=0.0066), respectively (P-value by two-sided Cochran-Armitage trend test). Univariate regression analyses identified MBDA score, DAS28-ESR and disease duration as predictors of flare at 52 weeks (p≤0.05). Conclusions: These findings suggest that the MBDA score could predict flare and SC-REM in RA patients in stable clinical remission, undergoing ADA withdrawal while maintaining MTX treatment. References: Hirata S, et al, Arthritis Res Ther. 2013;15:R135 Tanaka Y, et al, Ann Rheum Dis. 2015;74:389–395 Disclosure of Interest: S. Hirata Speakers bureau: AbbVie, Eisai, Bristol Meyers Squibb, S. Tang Employee of: Crescendo Bioscience Inc., C. Hwang Employee of: Crescendo Bioscience Inc., I. Miyagawa: None declared, S. Kubo: None declared, K. Nakano: None declared, S. Nakayamada: None declared, K. Saito: None declared, N. Defranoux Employee of: Crescendo Bioscience Inc., Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Chugai, MSD, Astellas, Novartis, Speakers bureau: Abbvie, Chugai, Astellas, Takeda, Santen, Mitsubishi-Tanabe, Pfizer, Janssen, Eisai, Daiichi-Sankyo, UCB, GlaxoSmithKline, Bristol-Myers